Going the Extra Mile: What Taxi Rides Tell Us About the Long-Hour Culture in Finance - Okat, Deniz; Vasudevan, Ellapulli V. (Management Science, 2023)
We analyze banks’ “protected-weekend” policies that restrict junior bankers from working during weekends. We use taxi rides from bank addresses in New York City to infer bankers’ working hours. We find the policies induced bankers to shift their work to late-night hours on weekdays. We then investigate whether such shifts in working hours affected the quality of work. After the policy, analysts of the policy-implementing banks make more errors in their earnings forecasts. They also herd more toward the consensus in their forecasts. We further provide evidence that junior bankers are the most adversely affected by the policy. This paper was accepted by Victoria Ivashina, finance. Supplemental Material: The data files and online appendix are available at https://doi.org/10.1287/mnsc.2023.4774 .